The Earth Charity Tradition of the Farming Community of Bukit Biru Village in Tenggarong in Perspective 'Urf - Pribadi, Guntur; Andaryu, Lilik (International Journal on Advanced Science, Education, and Religion, 2024)
Islam does not prohibit various kinds of social customs and cultural traditions, as long as they do not conflict with Islamic law and creed. The earth alms ritual which is held in several regions of the archipelago is a legacy of ancestors which is essentially a manifestation of human gratitude towards the Creator. In practice, many earth charity ritual ceremonies have now experienced acculturation with Islamic values, namely sharing the harvest accompanied by offering prayers to Allah SWT as an expression of gratitude. The tradition of giving alms to the earth by the residents of Bukit Biru Tenggarong sub-district aims to build togetherness among fellow farmers, namely as a form of gratitude for the good fortune and delicious harvests from the agricultural sector that Allah SWT bestows on the farming community. The earth alms tradition, viewed from the perspective of Islamic law, can be categorized as 'Urf. 'Urf is a habit that has long been preserved by society and which later became a custom. Apart from that, 'Urf also has the meaning of a habit or action that is considered good by society.